Analysis of cultural influence and context in the translation of literary texts (2017)
The aim of this work is to identify the cultural aspects that are involved in the translation process and identify the techniques used by translators beyond the theory in the translation of literary texts, take to account the culture and context elements that are behind the environment of the writers. Besides, this writing includes, apart from theories, the ideas of Modern Languages Students and the experience from a professional translator that allows to understand the real field of interpreting texts from a source language to a target language. Firstly, it exposes the objective of the research, and it is supported by results with other similar works and, of course, with theories from significant authors. Secondly, through a questionnaire, an interview and some observation forms, important conclusions about translation techniques, culture and context are found and they are described in a useful way, in order to understand the importance to know the techniques classification, the culture, the context, and grammatical and semantical knowledge when a translation is about to start.